Using cellulose nanofiber as filler of urea formaldehyde resin in plywood manufacture - samira barzali; laya jamalirad; farshid faraji; sahab hajazi (Iranian Journal of Wood and Paper Industries, 2015)
Abstract In this study, physical and mechanical properties of poplar (Populus nigra) plywood made by urea-formaldehyde resin along with nano fiber cellulose were studied. For this reason, the nanofiber cellulose as filler at five levels 0, 1, 3, 5 and 7% based on oven dry weight of resin were used. Physical and mechanical properties of the samples, including water absorption and thickness swelling after 2 and 24 hours immersion in water, bending strength and modulus of elasticity (parallel and perpendicular to surface grain) and bonding shear strength were measured. The results showed that increasing the amount of nano fiber cellulose improved the dimentional stability of the boards. Also increasing the amount of nano fiber cellulose increases the bending strength and modulus of elasticity parallel to surface grain. On the other hand, increasing the amount of nano fiber cellulose increases the bonding shear strength but no significant differences observed between the different treatments.